Antibacterial Activity and Flavonoids Content of Artemisia cina Berg. ex Poljakov Ethyl Acetate Extracts - Kasmiyati, Sri; Kristiani, Elizabeth Betty Elok; Herawati, Maria Marina; Sukmana, Andreas Binar Aji (Biosaintifika: Journal of Biology & Biology Education, 2021)
The medicinal plant-derived bioactive compounds have a potential for many biological activities, including antimicrobial activity. Artemisia cina is a medicinal plant from the Compositae family with the potential of having antitumor, antifungal, and antibacterial activity. This study aimed to determine the antibacterial activity and the flavonoid content of A. Cina’s ethyl acetate extract. Plants samples were extracted by ethyl acetate maceration method. Antibacterial activity was tested against Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) by a disk diffusion method using 25, 50, and 100 mg/l extract concentrations. The flavonoid contents (quercetin and kaempferol) were measured using High-Performance Liquid Chromatography. The extracts of diploid and polyploid A. cina displayed some antibacterial activity, with the Gram-negative bacteria being more resistant than the Gram-positive counterpart. However, no significant difference was observed between the diploid and polyploid extracts. As for the flavonoid content, the highest quercetin content (0.5501 mg/ml) was found in the polyploid A. cina (J), while the highest kaempferol content (0.5818 mg/ml) was observed in the diploid A. cina (KJT). Although A. cina is widely grown in Indonesia, compared to other Artemisia species, A. cina has not been widely studied, especially its antibacterial  potential and in related to its flavonoid content and the use of ethyl acetate as the extraction solvent.  This study reveals the potential of A. cina as a natural antibacterial agent.